Paediatric pulmonary disease—are we diagnosing it right? - Rajendran, Priya; Thomas, Silla Varghese; Balaji, Sarath; Selladurai, Elilarasi; Jayachandran, Ganesh; Malayappan, Aravind; Bhaskar, Adhin; Palanisamy, Sivaraman; Ramamoorthy, Thirumalani; Hasini, Sindhu; Hissar, Syed (Frontiers in Pediatrics, 2024)
Background It has been reported that differential diagnosis of bacterial or viral pneumonia and tuberculosis (TB) in infants and young children is complex. This could be due to the difficulty in microbiological confirmation in this age group. In this study, we aimed to assess the utility of a real-time multiplex PCR for diagnosis of respiratory pathogens in children with pulmonary TB. Methods A total of 185 respiratory samples [bronchoalveolar lavage (15), gastric aspirates (98), induced sputum (21), and sputum (51)] from children aged 3–12 years, attending tertiary care hospitals, Chennai, India, were included in the study. The samples were processed by N acetyl L cysteine (NALC) NAOH treatment and subjected to microbiological investigations for Mycobacterium tuberculosis (MTB) diagnosis that involved smear microscopy, Xpert® MTB/RIF testing, and liquid culture. In addition, DNA extraction from the processed sputum was carried out and was subjected to a multiplex real-time PCR comprising a panel of bacterial and fungal pathogens. Results Out of the 185 samples tested, a total of 20 samples were positive for MTB by either one or more identification methods (smear, culture, and GeneXpert). Out of these 20 MTB-positive samples, 15 were positive for one or more bacterial or fungal pathogens, with different cycle threshold values. Among patients with negative MTB test results (n = 165), 145 (87%) tested positive for one or more than one bacterial or fungal pathogens. Conclusion The results suggest that tuberculosis could coexist with other respiratory pathogens causing pneumonia. However, a large-scale prospective study from different geographical settings that uses such simultaneous detection methods for diagnosis of childhood tuberculosis and pneumonia will help in assessing the utility of these tests in rapid diagnosis of respiratory infections.